A Pilot Study of a Self-Determination Curriculum on Secondary Students - Askvig, Brent A.; Naslund, Melissa; Borisinkoff, Evan D.; Daigneault, Rebecca (Journal of the American Academy of Special Education Professionals, 2020)
Special educators routinely help students develop their self-determination skills. One way this has been achieved is to provide instruction to the student on how they can lead aspects of their individualized education program (IEP) meeting. A pre-post-post single group design was used in this study to examine if, and to what degree, the implementation of the Choicemaker (Martin et al., 1996) modified self-directed IEP curriculum impacted self-determination levels for nine high school students diagnosed with various disabilities such as specific learning disabilities, other health impairments, and mild intellectual disability. This study addressed students in rural communities who received special education services through a variety of service delivery formats. These students were taught how to lead and participate in their IEP meetings. Two measures of overall and subscale aspects of self-determination were used along with a global teacher rating of student participation. The results conveyed an increase in self-determination levels after students participated in their IEP meetings.